Environmental geomorphic hazards on the road and its solutions (Rezan River Road as an example) - قادر, م.م.یاسین عبداللە قادر (Sulaimani Journal for Humanities, 2025)
the research area is located between latitudes (35° 53' 0" to 35° 50' 0" ) North and longitudes ( 45° 0' 0" to 45° 10' 0" ) East. Geographically, the study area is situated northwest of the central district of Sulaimani and south of the Dukan district (Map 1). Geomorphological processes and environmental risks are closely interconnected, as geomorphological risks arise from the environmental interactions of regions. In this research, we attempt to focus on mass movement processes, which are considered one of the significant geomorphological processes that can cause changes in the environment of any area and become a source of risk for transportation routes. Both slow and rapid movements, fluvial erosion, and changes in vegetation cover due to natural and anthropogenic factors (human activities, agriculture, industry, and fires) contribute to creating a suitable and favorable environment for the activity of mass movement processes. The aim of this study is to demonstrate the role of both rapid and slow movements in creating risks for the transportation route. An attempt has been made to analyze these geomorphological processes in detail, and through the use of the ARC GIS program and satellite imagery, this aspect is clarified, and the causes and solutions are identified. The study has employed analytical and practical methods. Finally, we conclude that rapid movements, especially rockfalls and rock/boulder slides in mountainous and steep areas, pose the most significant risks, particularly on the road between the villages of Kani Bi, Gawrade, Zarzi, Yusuf Awa, Isabagi, Awdalan, and Hanjira. Slow movements, however, pose a lesser risk. Simultaneously, the activity of fluvial erosion processes also has an impact on the road.
Keywords: GeomorphologicalEnvironmental Risks Mass Movement Processes Transportation Route Geographic Information Systems and Remote Sensing (GIS RS); Water Erosion